Bulky 4, 6-disubstituted tetraphenylethene–naphthalimide dyad: synthesis, copolymerization, stimuli-responsive fluorescence and cellular imaging. (1st December 2016) - Hua, Qiong-Xin; Xin, Bo; Liu, Jun-Xia; Zhao, Ling-Xi; Xiong, Zu-Jing; Chen, Tao; Chen, Ze-Qiang; Li, Chong; Gong, Wen-Liang; Huang, Zhen-Li; Zhu, Ming-Qiang
Abstract : We report the design and synthesis of a tetraphenylethene substituted with naphthalimide at the 4, 6 positions, named NI-2TPE. NI-2TPE exhibits strong solvent-dependent emission properties with combined ICT and AIE characteristics in THF–H2 O systems. This probe was used directly on test papers to distinguish normal organic solvents using their emission colours under UV light based on its AIE and ICT nature. Thanks to the vinyl group in NI-2TPE, we synthesized a copolymer of NIPAM and NI-2TPE, termed P(NIPAM- co -NI-2TPE). The resulting polymer is highly soluble and fluorescent in water ( Φ F = 15.4%). Due to the well-known thermo-responsive character of NIPAM, P(NIPAM- co -NI-2TPE) exhibits an interesting fluorescence change in response to various temperatures. Due to the thermo-induced shrinking of the PNIPAM chain, the fluorescence intensity gradually increased from 20 to 34 °C. As the temperature further increased from 34 to 90 °C, the fluorescence intensity decreased sharply, which was caused by the well-known thermal effects. Furthermore, we synthesized a P(HEA- co -NI-2TPE–TPP acrylate) copolymer, in which HEA is a hydrophilic unit, TPP is a mitochondria label and NI-2TPE a fluorescent probe. The corresponding polymer probe is highly soluble in water with FLQY = 7% and we have further applied this probe as a mitochondria targeted imaging tracker in HeLa cells successfully.